Strategi Bauran Pemasaran 4P Dalam Menentukan Sumber Modal Usaha Syariah Pedagang Pasar di Sidoarjo - Desy Dwi Sulastriya Ningsih; M. Ruslianor Maika (Jurnal Ilmiah Ekonomi Islam, 2020)
This research discussed the two main reasons that could be affecting decisions market traders in choosing a source of their capital, which is based on the needs of business capital and marketing with marketing mix 4P. The data obtained through interviews with traditional market traders in the Sidoarjo district using the qualitative method from a phenomenology perspective. This study using primary data analyzed that processed in-app atlas.ti 9 to achieve the structure and efficient data. This study aims to determine the effect of the 4P Marketing Mix carried out by financial institutions in attracting traders to choose the source of their business capital and whether traders' knowledge of usury and Islamic financial institutions can change this decision. The conclusions obtained indicate that public knowledge about riba and Islamic banking does not influence in determining people's interest in choosing the source of business capital, while the marketing mix can attract traders in determining where they will make business resource loans.